STUDI PENINGKATAN PENGETAHUAN GURU MENGENAI SITASI DALAM PENYUSUNAN KARYA TULIS ILMIAH UNTUK MEMINIMALKAN PLAGIARISM - Sari, K.; Nilakusmawati, D. P. E.; Tastrawati, N. K. T.; Astuti, L. G.; Widana, I. N. (Buletin Udayana Mengabdi, 2017)
The purpose of this activities was to knowthe effect of giving training to increase teachers 'knowledge about plagiarisme and the rules of procedure of citation in writing a scientific paper. The activities carried out in SMK Farmasi Bintang Persada Denpasar and Tabanan, with the subject of activity was the teachers who are teach in that school i.e. 16 person of SMK Farmasi Bintang Persada Denpasar and 9 person of SMK Farmasi Bintang Persada Tabanan. This activity was workshop about plagiarism and citation in writing a scientific paper. The method used was one group pretest-posttest. Instruments used in these activities was pre-test and post-test. Based on the analysis of the pretest and posttest scores, the result of this activity was there were a significant improvement on the knowledge of the teachers on plagiarism and the rules of procedure of citation in writing scientific paper after have got the workshop.